2007
DOI: 10.1099/ijs.0.64921-0
|View full text |Cite
|
Sign up to set email alerts
|

Halorubrum arcis sp. nov., an extremely halophilic archaeon isolated from a saline lake on the Qinghai–Tibet Plateau, China

Abstract: A Gram-negative, aerobic, neutrophilic and extremely halophilic archaeon (strain AJ201 T ), isolated from Ayakekum salt lake on the Qinghai-Tibet Plateau, was investigated by a polyphasic approach. The DNA G+C content of strain AJ201 T was 65.7 mol%. The major polar lipid profile and phylogenetic analysis based on 16S rRNA gene sequences supported the allocation of the strain to the genus Halorubrum. The results of DNA-DNA hybridizations and physiological and biochemical tests allowed genotypic and phenotypic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
17
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…However, these strains were isolated from three different geographic regions of Asia at three different time points (Zvyagintseva and Tarasov, 1987; Ventosa et al, 2004; Cui et al, 2007; Xu et al, 2007), from Chinese solar salterns to Turkmenistani saline soils. While the role of geography and ecology in haloarchaeal speciation is unsettled (Oh et al, 2010; DeMaere et al, 2013; Dillon et al, 2013; Zhaxybayeva et al, 2013) all four of the named species have undergone polyphasic characterization, including DNA-DNA hybridization (Ventosa et al, 2004; Cui et al, 2007; Xu et al, 2007). Presumably, if these taxa lived in the same environments and exchanged genes with each other in a positively biased manner like phylogroups A and B, they would be homogenized and indistinguishable by current polyphasic description processes.…”
Section: Discussionmentioning
confidence: 99%
“…However, these strains were isolated from three different geographic regions of Asia at three different time points (Zvyagintseva and Tarasov, 1987; Ventosa et al, 2004; Cui et al, 2007; Xu et al, 2007), from Chinese solar salterns to Turkmenistani saline soils. While the role of geography and ecology in haloarchaeal speciation is unsettled (Oh et al, 2010; DeMaere et al, 2013; Dillon et al, 2013; Zhaxybayeva et al, 2013) all four of the named species have undergone polyphasic characterization, including DNA-DNA hybridization (Ventosa et al, 2004; Cui et al, 2007; Xu et al, 2007). Presumably, if these taxa lived in the same environments and exchanged genes with each other in a positively biased manner like phylogroups A and B, they would be homogenized and indistinguishable by current polyphasic description processes.…”
Section: Discussionmentioning
confidence: 99%
“…Phylogenetic analysis based on 16S rRNA gene sequences revealed that strain CGSA15 T was a member of the genus Franzmann et al, 1988). At the time of writing, Halorubrum is the largest genus within the family Halobacteriaceae, with 19 recognized species, three of which are alkaliphilic and 16 neutrophilic Xu et al, 2007;Castillo et al, 2007). Of the three alkaliphilic species, Halorubrum vacuolatum was isolated from Lake Magadi, Kenya (Mwatha & Grant, 1993), Halorubrum tibetense from Lake Zabuye, Tibet, China (Fan et al, 2004), and…”
mentioning
confidence: 99%
“…At the time of writing, Halorubrum is the largest genus within the family Halobacteriaceae, with 19 recognized species, three of which are alkaliphilic and 16 neutrophilic Xu et al, 2007;Castillo et al, 2007). Of the three alkaliphilic species, Halorubrum vacuolatum was isolated from Lake Magadi, Kenya (Mwatha & Grant, 1993), Halorubrum tibetense from Lake Zabuye, Tibet, China (Fan et al, 2004), and Halorubrum alkaliphilum from a soda lake of Xinjiang, China (Feng et al, 2005).…”
mentioning
confidence: 99%
“…orientale (Castillo et al, 2006), Hrr. arcis (Xu et al, 2007), Hrr. litoreum (Cui et al, 2007) and Hrr.…”
mentioning
confidence: 99%
“…The haloarchaeal primers used for the PCR were HK 1F (ATTCCGGTTGATCCTGCCGG) and H1492R (GTTACCTTGCCCGTTCCTTC) (Litchfield et al, 2005). The almost complete 16S rRNA gene sequence (1436 bp) of strain SF3-213 T was determined and com- Cui et al (2006Cui et al ( , 2007, Castillo et al (2006Castillo et al ( , 2007 and Xu et al (2007). +, Positive; 2, negative; +/2, doubtful; ND, no data available.…”
mentioning
confidence: 99%